Proof of X-repute blockchain consensus protocol for IoT systems. Issue 95 (August 2020) - Wang, Eric Ke; Sun, RuiPei; Chen, Chien-Ming; Liang, Zuodong; Kumari, Saru; Khurram Khan, Muhammad
Abstract: Recently, blockchain technology has been used to address the security issues of Internet of things (IoT) applications. However, some issues particular to blockchain should be solved to meet the security requirements of IoT systems. The core of blockchain technology is distributed computing, along with the collaboration mechanism of group trust under the distributed computing environment, which can solve the scalability, collaboration ability, trust relationship, and security protection challenges faced by the IoT. The existing blockchain consensus protocol can only solve the trust cooperation problem with limited credibility. Although distributed trust relationship management has advantages over centralized trust relationship management, several risks exist. Here, the most critical issue is the credibility of the blockchain consensus protocol. Based on the characteristics of the traditional public chain, we propose a repute-based consensus protocol for blockchain-enabled IoT systems. In the protocol, two methods are designed to enable the blockchain system to reach a consensus rapidly and safely. The repute rewards and punishments method settles the repute values of nodes; nodes with satisfactory behavior receive repute rewards. The repute mining method proposes repute requirements for consensus nodes; nodes with high repute value produce blocks more easily. Security analysis has been conducted using a theory model and experimental evaluation. The establishment of our repute system can improve the consensus protocol, resisting stronger attacks, and giving several users with lower computing power a greater opportunity to participate in consensus. The experimental results show that the repute-based consensus protocol has advantages in terms of security and that its resistance capability against attacks is improved.